The impact of within country heterogeneity in vocational specificity on initial job matches and job status - Vogtenhuber, Stefan [Verfasser] (My University, 2014)
"This paper analyses the impact of vocational specificity on school-to-work transitions in terms of initial job mismatches and socioeconomic status at the individual level. Considering heterogeneity amongst the various qualifications in Austria, the study finds that the positive impact of specificity on initial labour market placement known from cross-country research also holds within the highly stratified Austrian system in which various vocational specialisations are provided at the upper secondary level. Independent of the level and field of the qualification obtained, vocational specificity facilitates initial labour market placement, resulting in a reduced mismatch risk and an increase in initial jobs status. In the course of subsequent labour market adjustments, however, holders of general qualifications attain higher status gains when changing jobs. Likewise, the overqualified can make up for a good part of their initial status penalty on labour market entrance through job changes. Implications for policy and practice are discussed." (Authors' abstract, BIBB-Doku)
Keywords: G 1.2.3 Qualifikationsentwicklungen; G 1.3.2.2.3 Zweite Schwelle, in Arbeit; G 2.4.1 Bildungs- und Berufswege; I 2.2.1 Westeuropa; Berufsstruktur; Berufsanfänger; Berufseinmündung; Zweite Schwelle; Spezialisierung; Adäquate Beschäftigung; Mismatch; Beruflicher Status; Überqualifikation; Österreich